Experimental investigation on subcooling of liquid hydrogen by helium gas injection through evacuation. Issue 8 (26th July 2021) - Starvin, M. S.; Edwin, M.; Kumaresan, K.
Abstract: Subcooling is the process of bringing down the temperature of liquids lower than that of the boiling point of the corresponding vapor pressure. The performance of subcooling of cryogenic liquids mainly depends on the heat‐inleak of the system, the helium injection mass flow rate, helium injection temperature, and helium injection nozzle pattern. This paper presents an alternative method, by making use of the least heat in the leakage of the liquid hydrogen storage container, which is quite possible because containers with excellent thermal insulation are commercially available nowadays. The process involved is rapid evacuation through gas ejectors, thus reducing the effect of temperature. The advantage and the process of evacuation leading to subcooling in a unique manner are the objective of this article. The experimental results are discussed in comparison with the thermophysical process involved in the subcooling operation. A comparative study is also carried out with the theoretical heat exchange process in which helium is used as a medium for the economy of the stated process. It is stated that the current process of subcooling through evacuation is superior to the conventional heat exchange process.